Poly[tetraaqua-μ(4)-squarato-di-μ(3)-squarato-disamarium(III)] - Akkari, Hocine (International Union of Crystallography, 2008)
The structure of the title compound, [Sm(2)(C(4)O(4))(3)(H(2)O)(4)](n), consists of infinite-chain structural units, built from edge-sharing samarium SmO(7)(H(2)O)(2) polyhedra and linked via bis-monodendate squarate (sq1) groups. The chains extend along [100] in a zigzag mode and are interconnected by bis-chelating squarate (sq2) ligands into layers parallel to (101). Interlayer hydrogen bonds strengthen the cohesion of the three-dimensional network. The samarium cation is coordinated by four O atoms from sq1 units and three O atoms from sq2 units, in addition to two water O atoms. The best representation of the samarium SmO(7)(H(2)O)(2) polyhedron is distorted tricapped trigonal-prismatic. The sq1 ligand has one metal-free O atom and relates three Sm atoms in a bis-monodentate and chelation fashion, the second squarate, sq2, is strictly centrosymmetric and acts as a bis-chelating ligand.